If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 180 + -30 + -1(4x + 2) = 180 + -1(8 + 6x) Reorder the terms: 180 + -30 + -1(2 + 4x) = 180 + -1(8 + 6x) 180 + -30 + (2 * -1 + 4x * -1) = 180 + -1(8 + 6x) 180 + -30 + (-2 + -4x) = 180 + -1(8 + 6x) Combine like terms: 180 + -30 = 150 150 + -2 + -4x = 180 + -1(8 + 6x) Combine like terms: 150 + -2 = 148 148 + -4x = 180 + -1(8 + 6x) 148 + -4x = 180 + (8 * -1 + 6x * -1) 148 + -4x = 180 + (-8 + -6x) Combine like terms: 180 + -8 = 172 148 + -4x = 172 + -6x Solving 148 + -4x = 172 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 148 + -4x + 6x = 172 + -6x + 6x Combine like terms: -4x + 6x = 2x 148 + 2x = 172 + -6x + 6x Combine like terms: -6x + 6x = 0 148 + 2x = 172 + 0 148 + 2x = 172 Add '-148' to each side of the equation. 148 + -148 + 2x = 172 + -148 Combine like terms: 148 + -148 = 0 0 + 2x = 172 + -148 2x = 172 + -148 Combine like terms: 172 + -148 = 24 2x = 24 Divide each side by '2'. x = 12 Simplifying x = 12
| 180-30-4x+2=180-8+6x | | 26x+12y=24.5 | | 5/x=x/8 | | y=sinx(1-cosx) | | 2(x+5)=x+30 | | x+21=94 | | 2(x-5)=x+30 | | (x+3)*(x+4)*(x+5)=0 | | (x+3)*(x+4)*(x-5)=0 | | 10/7x=-1 | | x+22=134 | | -7x+23=-14x+79 | | (2.5-Z)/(2.5-1)=0.66 | | 4x^2=x^2+135 | | 0.3a^2b-ba^2= | | 3x+05=2x | | 2(x+1)-4(x-1)=10 | | 7x-17=-11 | | 4(5n-7)=10x+2 | | .5=logx | | 9-x=3^1/2 | | 2^x=1/128 | | 1=4tan(2x+1)-1 | | x+1*2x-1= | | 5x+14=14-9x | | 2x+51=3x+54 | | ax=5x+11 | | z+81=97-7 | | 6/7=u/12 | | 2(sin^6x+cos^6x)-3(sin^4x+cos^4x)=-1 | | f(7-x)=3(7-x)+7 | | 6.25=-0.5 |